PENGUATAN MODERASI BERAGAMA MELALUI LITERASI DIGITAL BAGI GENERASI MILENIAL DI TULUNGAGUNG - Nahdhiyanto, Ahmadi Abdul Shomad Faiz; Zatadini, Galuh Indah (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
The digital era has significantly transformed the pattern of religious information consumption, particularly among millennials. The high accessibility of digital information necessitates strong digital literacy to enable individuals to critically and moderately assess religious narratives. This study aims to analyze the impact of digital literacy on the understanding of religious moderation among millennials in Tulungagung and to formulate strategies to enhance digital literacy to strengthen religious moderation. Using a qualitative approach with a descriptive-analytical method, this study found that the level of digital literacy among millennials in Tulungagung varies. Factors such as education, access to credible sources, and the role of religious communities influence their understanding of religious moderation. The proposed strategies include integrating digital literacy into education, strengthening the role of religious organizations, and engaging religious figures in digital platforms. With a systematic implementation of these strategies, digital literacy can serve as a crucial instrument in reinforcing religious moderation values in the digital age.